Art and Copyright Law - Walter, Giulia (Taylor & Francis, 2025)
This book tackles the lack of synchronicity between art and copyright law, proposing practical and interdisciplinary tools through which to navigate this conflict. In the last decades, high profile lawsuits have been filed against artists accused of plagiarism including Jeff Koons, Barbara Kruger and Andy Warhol. This book demonstrates how these cases are at odds with contemporary artistic reality, in which the use of antecedent visual forms is common practice. Focusing on the dichotomies of “original/copy” and of “old/new”, this work addresses this phenomenon from both theoretical as well as legal perspectives. Using Swiss copyright law as the main case study, the book comparatively assesses other international legal frameworks. Through understanding the origins of the conflict between art and copyright, the book highlights solutions to navigate copyright cases with a new methodological approach. The book will be of interest to researchers in the field of art and copyright law, intellectual property and art.